2021
DOI: 10.3390/plants10112460
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Phytomediated Silver and Gold Nanoparticles Synthesised from Rooibos (Aspalathus linearis), and Aspalathin

Abstract: The green chemistry approach has continuously been applied for the synthesis of functional nanomaterials to reduce waste, environmental hazards, and the use of toxic chemicals among other reasons. Bioactive natural compounds have been found great potential in this regard and are used to improve the stability, activity, and biodistribution of metal nanoparticles (MNPs). Aspalathin (ASP) from Aspalathus linearis (rooibos) has a well-defined pharmacological profile and functional groups capable of both reducing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Akinfenwa et al reported a procedure in which optimum concentration (10 mL of aqueous 5% each) of green rooibos extract, and aspalathin compound were added to a 90 mL of 1 mM heated solution of respective gold and silver precursors while stirring at 70°C. A similar procedure for zinc oxide nanoparticles where 25 mL of aqueous 1% mango seed extract was added to 75 mL of 10 mM zinc nitrate solution maintained at 30°C in an orbital shaker was described by Rajeshkumar et al [35,36]. Contrarily, different concentrations of the metal precursor are added to a predetermined concentration of phytochemicals.…”
Section: Phytochemicals In Metallic Nanoparticles Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Akinfenwa et al reported a procedure in which optimum concentration (10 mL of aqueous 5% each) of green rooibos extract, and aspalathin compound were added to a 90 mL of 1 mM heated solution of respective gold and silver precursors while stirring at 70°C. A similar procedure for zinc oxide nanoparticles where 25 mL of aqueous 1% mango seed extract was added to 75 mL of 10 mM zinc nitrate solution maintained at 30°C in an orbital shaker was described by Rajeshkumar et al [35,36]. Contrarily, different concentrations of the metal precursor are added to a predetermined concentration of phytochemicals.…”
Section: Phytochemicals In Metallic Nanoparticles Synthesismentioning
confidence: 99%
“…Also, Elbagory et al previously reported a method, for large-scale screening of plants with microtitre-plate. Through this method, the authors determined the optimum concentration for the biosynthesis of gold nanoparticles for further scale-up [36][37][38]. PM-NPs can also be synthesized by mixing plant extract clear solution with a predetermined concentration of the metal solution and boiling the above mixture at desired time and temperature while mixing.…”
Section: Phytochemicals In Metallic Nanoparticles Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, AuNPs and AgNPs have been widely studied due to their low toxicity to normal cells compared to other metal nanoparticles [ 7 ]. Their anticancer properties have been tested in vitro toward various types of cancer cells, such as breast cancer [ 70 , 71 ], lung cancer [ 64 , 76 ], liver cancer [ 66 , 86 ], cervical cancer [ 64 ], colon cancer [ 62 , 87 ], and human neuroblastoma cells [ 86 ]. Several studies have proven that plant-based AuNPs and AgNPs have anticancer biological activity, as shown in Table 3 .…”
Section: Synthesis Of Gold and Silver Nanoparticles Using Plant Extractsmentioning
confidence: 99%
“…There were no reports on the use of the synthesised ZnO NPs for any applications; therefore, further studies can also include the application of synthesised ZnO NPs. In addition to being used for the synthesis of ZnO NPs, A. linearis has been documented in the synthesis of various NPs, including Co 3 O 4 NPs [96], Au NPs [98], Eu 2 O 3 [100], Ag NPs [101] Pd NPs, PdO NPs [102], Rh NPs [103], RuO 2 NPs [104], SnO 2 NPs [105], and NiO NPs, [106]. The synthesised NPs were assessed for applications in photodegradation of dyes, water splitting and biological application.…”
Section: Aspalathus Linearismentioning
confidence: 99%